Maternal vaginal fluids play a major role in the colonization of the neonatal intestinal microbiota - Xie, Jingxian; Tang, Chen; Hong, Shouqiang; Xin, Yuntian; Zhang, Jie; Lin, Yi; Mao, Lindong; Xiao, Yunshan; Wu, Quanfeng; Zhang, Xueqin; Shen, Heqing (Frontiers in Cellular and Infection Microbiology, 2023)
Background Caesarean section (CS) is associated with newborns’ health risks due to the blocking of microbiome transfer. The gut microbiota of CS-born babies was different from those born vaginally, which may be attributed to reduced exposure to maternal vaginal microbes during labour. To understand the microbial transfer and reduce CS disadvantages, the effect of vaginal microbiota exposure on infant gut microbiota composition was evaluated using 16s rDNA sequencing-based techniques. Results Pregnant women were recruited in the Women and Children’s Hospital, School of Medicine, Xiamen University from June 1st to August 15th, 2017. Maternal faeces (n = 26), maternal vaginal fluids (n = 26), and neonatal transitional stools (n = 26) were collected, while the participants underwent natural delivery (ND) (n = 6), CS (n = 4) and CS with the intervention of vaginal seedings (I) (n = 16). 26 mothers with the median age 26.50 (25.00-27.25) years showed no substantial clinical differences. The newborns’ gut microbiota altered among ND, CS and I, and clustered into two groups (PERMANOVA P = 0.001). Microbial composition of ND babies shared more features with maternal vaginal samples (PERMANOVA P = 0.065), while the microbiota structure of ND babies was obviously different from that of sample of maternal faeces. The genus Bacteroides in CS-born babies with intervention approached to vaginal-born neonates, compared with CS-born neonates without intervention. Conclusions Neonatal gut microbiota was dependent on the delivery mode. And the gut microbiota CS newborns with vaginal seeding shared more features with those of ND babies, which hinted the aberrant gut microbiota composition initiated by CS might be partly mitigated by maternal vaginal microbiota exposure.